Associação do câncer de mama com a infecção pelo papilomavírus humano (HPV): evidência molecular - Cavalcante, José Roosivelt (2018)
Breast cancer is the most common cancer among women worldwide. Approximately 1.79 million new cases were expected for 2015 with 560,407 deaths estimated for this same year in the planet. In Brazil, for each year of the 2018-2019 biennium, some 59,700 new cases of breast cancer were predicted. Although some risk factors such as age, hormones, alcohol, diet and family history are associated with breast cancer, for the majority of cases the initial cause remains unexplained. The viral etiology for breast cancer has been considered and the identification of a possible viral agent related to this disease has been a source of motivation for researchers for decades. Human papillomavirus (HPV), besides being present in more than 99% of cervical carcinomas, is already considered to be a major risk factor for many penile, vulvar, vaginal and anal carcinomas and a growing fraction of head and neck squamous cell carcinomas. The HPV presence in breast cancer tissue has been already reported in recent studies. The aim of this study was to investigate the occurrence and the predominant type of HPV in breast cancer tissue. METHODS: One hundred three cases of breast carcinomas and ninety-five normal breast samples, as a non-malignant control group, were examined by a nested polymerase chain reaction (PCR) with the MY09/MY11 and GP5+/GP6+ primers targeting the L1 region of HPV, followed, in a second round, by a nested a multiplex PCR (NMPCR) with type specific primers for the E6-E7 region of the HPV.RESULTS: The HPV DNA was detected in 49,5% breast carcinoma and in 15,8% normal breast (p < 0,0001). HPVs 6/11 were found in 13.7% of HPV positive breast cancers. HPV positive breast cancers were observed more frequently in the younger women (<42 years). CONCLUSION: The high proportion of HPV positive breast cancers detected in this study and its presence, not rare, in breasts of women without cancer may indicate a likely causal role for HPV in human breast cancer. Keywords: Breast neoplasms, Human papillomavirus, HPV, Polymerase chain reaction, PCR.